x^2+2x+6x+12=x+6

Simple and best practice solution for x^2+2x+6x+12=x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x^2+2x+6x+12=x+6 equation:



x^2+2x+6x+12=x+6
We move all terms to the left:
x^2+2x+6x+12-(x+6)=0
We add all the numbers together, and all the variables
x^2+8x-(x+6)+12=0
We get rid of parentheses
x^2+8x-x-6+12=0
We add all the numbers together, and all the variables
x^2+7x+6=0
a = 1; b = 7; c = +6;
Δ = b2-4ac
Δ = 72-4·1·6
Δ = 25
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{25}=5$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(7)-5}{2*1}=\frac{-12}{2} =-6 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(7)+5}{2*1}=\frac{-2}{2} =-1 $

You can always share this solution

See similar equations:

| 3x=4x+47 | | 0=2x2-23x-39 | | (3x-2)+2x+5)=180 | | 35=x-46 | | 4x+47=3 | | 15+2x-1x=60 | | -4(3x+7)=-172 | | 3.1x=55.8 | | y-26=30 | | –6u–8=–2u–12 | | 9(-7-3x)=18=x= | | –4u–8=–12 | | x*30/100=500 | | -(10-x)=-13=x= | | (2b+12)26=(2b+5)26 | | 4x+3x=47° | | 74+i=592 | | A=12/6b+17.7 | | 3x+30+x=10+2x+5x2 | | 11+3x=-4-2x=x= | | 38.95=22.50+s | | 2-x/0.3=14 | | 22+5x=-8-x=x= | | 13=u-22 | | 18-4x=-9-x=x= | | 128+x=350 | | 8-2x=11+x=x= | | Y=1/4x+10 | | 0.1x=+14 | | (h-8^2=0 | | 25+20x=-5+5x=x= |

Equations solver categories